Restructuring of Debt Payment Obligation Suspension Agreements Homologated Due to Covid-19 Non-Natural Disasters - Labibah, Hanin Alya' (Al-Risalah, 2022)
The quick spread of the Covid-19 pandemic weakened the economy and led to the non-performance of debtors’ obligations because their business did not run smoothly during the period. Several business actors with homologated PKPU peace were hindered or prevented from achieving their aims including the force majeure qualifications associated with the Covid-19 pandemic. Therefore, this normative legal research conducted through statutory, conceptual, and case approaches was used to assess this situation. The findings showed that a debtor can request to restructure the homologation implementation based on the force majeure of the Covid-19 pandemic but the request needs to be based on the agreement between the debtor and creditor using Article 1338 paragraph (1) of the Civil Code as the premise. It was discovered from the PT Berlian Tenker case that the agreement was conducted without requiring further re-homologation in the court because the UUK-PKPU is not applicable in the matter due to the fact that the Covid-19 pandemic is a national disaster classified as a relative force majeure.